Multiple sclerosis : 300 tips for making life easier - Schwarz, Shelley Peterman (Demos Medical Pub., 2006)
This completely revised second edition of Multiple Sclerosis: 300 Tips for Making Life Easier contains tips, techniques, and shortcuts to help MS patients organize and simplify their lives. With over 300 tips readers will learn to conserve valuable time and energy, develop techniques for making life easier, so they can enjoy life to the fullest. From basic principles to unique solutions for saving time and energy to specific ideas, this book is packed with helpful information for those coping with the special challenges of a chronic illness. Updated chapters cover Home Safety and Accessibility.